2023
DOI: 10.1021/acs.inorgchem.3c00819
|View full text |Cite
|
Sign up to set email alerts
|

Half-Sandwich Ruthenium Complexes with Hydrazone Ligands: Preparation, Structure, and Catalytic Activity in Cyanosilylether Synthesis under an Air Atmosphere

Abstract: A new class of N,O-coordinate half-sandwich ruthenium complexes supported by hydrazone ligands with a general formula of [Ru(η 6p-cymene)Cl(L)] have been obtained in moderate to excellent yields conveniently. These air-and moisture-stable ruthenium complexes exhibited excellent catalytic activity in cyanosilylether synthesis under mild reaction conditions. Under the catalysis of ruthenium, various cyanosilylethers with different substituents were obtained through a one-pot reaction of trimethylsilyl cyanide wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The stretch bands at approximately 1349–1360 cm −1 suggested the coordination of the C–O bond to the iridium center through the enolization configuration. 21 In the 1 H NMR spectra of the prepared iridium complexes 1–4 , the disappeared peaks of –OH protons of the free ligand in the range of δ 9.0 ppm indicated that the hydrazone ligands underwent deprotonation during the reaction with the iridium precursor. Multiple groups of signals were observed in the range of δ 7.00–8.50 ppm due to the aromatic protons of the hydrazone ligands of the iridium complexes.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The stretch bands at approximately 1349–1360 cm −1 suggested the coordination of the C–O bond to the iridium center through the enolization configuration. 21 In the 1 H NMR spectra of the prepared iridium complexes 1–4 , the disappeared peaks of –OH protons of the free ligand in the range of δ 9.0 ppm indicated that the hydrazone ligands underwent deprotonation during the reaction with the iridium precursor. Multiple groups of signals were observed in the range of δ 7.00–8.50 ppm due to the aromatic protons of the hydrazone ligands of the iridium complexes.…”
Section: Resultsmentioning
confidence: 98%
“…9–20 Although various types of catalytic systems have been developed, drawbacks such as the instability of the catalyst, harsh conditions, and narrow substrate scope have limited their applications. Recently, our group reported the ruthenium-catalyzed cyanosilylation reaction; 21 however, there are relatively few reports of hydrazone-based N , O -chelate half-sandwich iridium complexes as catalysts to catalyze the cyanosilylation reaction. This motivated us to explore a new type of catalyst for stable, simple synthesis, and efficient catalysis of the iridium complex.…”
Section: Introductionmentioning
confidence: 99%
“…The Ru–N (2.10 Å) and Ru–O (2.06 Å) bond lengths were located in the regular range compared with the reported analogous complexes. 24…”
Section: Resultsmentioning
confidence: 99%